2014
DOI: 10.1093/gerona/glu028
|View full text |Cite
|
Sign up to set email alerts
|

Brain-Derived Neurotrophic Factor Plasma Levels: Relationship With Dementia and Diabetes in the Elderly Population

Abstract: The mechanisms linking diabetes and cognitive impairment/dementia, two common conditions of elderly people, are not completely known. Brain-derived neurotrophic factor (BDNF) has antidiabetic properties, and reduced circulating BDNF was associated with dementia. We investigated the relationship between plasma BDNF levels, dementia, and diabetes in a sample of 164 community-dwelling elderly individuals, including 50 participants with vascular dementia, 44 with late onset Alzheimer's disease, 23 with cerebrovasc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 70 publications
1
41
1
1
Order By: Relevance
“…A recent cohort study showed that high glucose levels may be a risk factor for dementia and that the combination of DM2 and hypertension greatly increase the risk of cognitive impairment. Beside vascular factors, other risk factors include the formation of advanced glycosylation products, oxidative inflammation and stress, alterations in the hypothalamic-pituitary-adrenal axis and cortisol levels[30], and abnormalities in insulin secretion and signaling that promote cerebral amyloidosis.…”
Section: Discussionmentioning
confidence: 99%
“…A recent cohort study showed that high glucose levels may be a risk factor for dementia and that the combination of DM2 and hypertension greatly increase the risk of cognitive impairment. Beside vascular factors, other risk factors include the formation of advanced glycosylation products, oxidative inflammation and stress, alterations in the hypothalamic-pituitary-adrenal axis and cortisol levels[30], and abnormalities in insulin secretion and signaling that promote cerebral amyloidosis.…”
Section: Discussionmentioning
confidence: 99%
“…Brain-derived neurotrophic factor (BDNF) has antidiabetic properties, and reduced circulating BDNF is linked to dementia (Passaro et al, 2015). In the elderly, there may be a synergistic effect of cognitive decline and diabetes on reducing BDNF levels (Passaro et al, 2015).…”
Section: Osa Upregulates Glucosementioning
confidence: 99%
“…Crossing bi-directionally the blood-brain barrier, BDNF can act at a systemic level. Low levels of plasma BDNF have been associated with dementia [10, 11], diabetes [1113], depression [14, 15] and coronary syndrome [16]. …”
Section: Introductionmentioning
confidence: 99%